2011
DOI: 10.2485/jhtb.20.231
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenin-Induced Periodontitis as an Experimental Model in Rats Analyzed by Micro-Computerized Tomography

Abstract: Periodontitis is a common disease worldwide and is a cause of tooth loss. For these reasons, many investigators have examined periodontitis not only by in vivo studies but also in vitro studies. For in vivo studies, it is very important which animal is used and how to make experimental periodontitis easily and efficiently in animals. Although the process of periodontitis in monkeys and dogs is similar to that in humans, rats and mice are much more useful animals for experiments because of ease of handling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This study uses ligature‐induced experimental periodontitis, which is a well‐established model of experimental periodontitis in rats and a simple and reliable technique for disease induction. Rat models are commonly used in experimental periodontitis studies, due to the similarities in structure and organization of the periodontal tissues to those of humans 35‐37 …”
Section: Discussionmentioning
confidence: 99%
“…This study uses ligature‐induced experimental periodontitis, which is a well‐established model of experimental periodontitis in rats and a simple and reliable technique for disease induction. Rat models are commonly used in experimental periodontitis studies, due to the similarities in structure and organization of the periodontal tissues to those of humans 35‐37 …”
Section: Discussionmentioning
confidence: 99%
“…We verified cardiac and respiratory arrest. We used a previously reported carrageenan-induced rat model of periodontitis (27). While the rats were under anesthesia, buccal and lingual gingiva were exfoliated using an explorer.…”
Section: Quantitative Reverse Transcription-polymerase Chain Reaction...mentioning
confidence: 99%
“…In addition, it is reported that NOS inhibition prevents alveolar bone resorption 42) . According to these findings, it seems that the application of PRPs to periodontitis with weak bone loss may achieve more effective results, although the authors applied PRPs to periodontitis with heavy alveolar bone loss 23) . For this reason, further additional experiment may be necessary in future.…”
Section: Discussionmentioning
confidence: 99%
“…The carrageenin-induced experimental periodontitis model 23) was used in this study. Briefly, the buccal gingiva of the right mandibular first molar of six male rats (control group n=3, …”
Section: Experimental Periodontitismentioning
confidence: 99%
See 1 more Smart Citation